FEATURES OF THE BEHAVIOR OF LUBRICANT MATERIAL IN TEXTURED REGIONS UNDER BOUNDARY FRICTION - Marchuk, Volodymyr; Mikosianchyk, Oksana; Marchuk, Vyacheslav (Problems of Friction and Wear, 2026)
Prospects for the formation of a textured surface on tribological elements (tribo-pairs) were analyzed. The goal of this work is to construct a mathematical model for the location of a lubricant droplet both within the depressions (dimples) of the textured surface and outside of them, depending on kinematic factors, structural characteristics of the surface, and properties of the lubricant. The mathematical model for the movement of an oil droplet in a single dimple of the textured surface is based on the influence of centrifugal force, the force of gravity, and the surface tension force of the oil on the droplet during friction. A limit condition has been established at a sample rotation frequency greater than $27 \text{ rpm}$, under which the oil droplet "leaves" the dimple at the upper position of the sample and remains in the space between the sample and the counter-body surface, ensuring the regeneration of the boundary lubricating film on the tribocontact surface when it breaks down. When the sample rotation frequency is reduced to $26.8 \text{ rpm}$, the oil droplet remains in the dimple and does not affect the processes of lubricating film regeneration. The modeling results will make it possible to predict the oil-holding capacity (oil retention) of the textured surface dimples, which will contribute to increasing the wear resistance of the contact surfaces during the regeneration of the boundary lubricating layer.